Preventive Behavior to Obesity in Elementary School Students in Surabaya, Indonesia - Rif'atin Haibah; Muji Sulistyowati; Ismayani Ismayani (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2020)
Background: Overweight and obesity are two of the main non-communicable disease risks, causing mortalities in developed and developing countries. Obesity is a condition of excessive body fat, which causes overnutrition and obesity in children increases each year. Child obesity raises physical health problems that have the impact on the quality of life and the child’s body development. Moreover, it potentially makes children suffer from diseases. Purpose: This study aims to identify the related factors of preventive behavior for obesity among elementary school students in Surabaya by using the Health Belief Model Theory. Methods: This study was a cross-sectional study, which involved 104 elementary school students in fourth and fifth grade in SD Dr. Soetomo V, Surabaya as samples. These samples were taken with simple random sampling. The independent variables in this study were perceived susceptibility, perceived severity, perceived benefits, perceived barriers, self-efficacy and cues to action. While the dependent variable was preventive behavior for obesity. Data were analyzed by using double logistic regression after the candidates selectionwith p<0.25 was obtained from the analysis of dependent and independent variables. Results: The results show that perceived susceptibility (P Value= 0,262), perceived severity (P Value= 0,967), perceived barriers (P Value= 0,255), and cues to action (P Value= 0,565) does not have a correlation with preventive behavior for obesity among the students. Factors related to preventive behavior for obesity were perceived benefits (P Value= 0,037) and self-efficacy (P Value= 0,037). Conclusion: The factors which are related to preventive behavior for obesity among the students at Dr. Soetomo V Elementary School, Surabaya are perceived benefits and self-efficacy.